Monocyte Levels, Education, and Consanguinity Associated With Miscarriage Risk: Tingkat Monosit, Pendidikan, dan Konsanguitas Berhubungan dengan Risiko Keguguran - Azeez, Fatima Sadiq; Salman, Ali Naeem (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Miscarriage remains a major public health concern with multifactorial etiology encompassing biological, social, and environmental influences. Specific Background: While numerous studies have examined hormonal, chromosomal, and nutritional contributors, the role of hematological and socio-demographic factors such as monocyte activity, consanguinity, and education level is underexplored. Knowledge Gap: The diagnostic and predictive significance of these variables in spontaneous abortion remains unclear. Aim: This study aimed to investigate the association between miscarriage and hematological parameters—particularly monocyte and platelet counts—as well as consanguinity and educational status. Results: Analysis of 100 participants (50 miscarriage cases and 50 controls) revealed a statistically significant elevation in monocyte count (P = 0.004) among miscarriage cases, while other parameters such as platelet count, RBC, Hb, and MCV showed no significant differences. Additionally, consanguinity (P = 0.04) and lower education levels (P = 0.026) were significantly associated with miscarriage incidence. Novelty: The study provides novel evidence supporting monocyte elevation and socio-demographic risks as contributory factors in miscarriage. Implications: These findings suggest the potential for monocyte levels and socio-educational context to serve as supplementary markers for miscarriage risk, advocating for integrated hematological and socio-demographic screening in early prenatal care. Highlights: Monocyte elevation was significantly linked to miscarriage cases, suggesting a possible inflammatory response. Consanguineous marriage showed a statistically significant association with higher miscarriage rates. Low educational attainment was strongly correlated with increased risk of miscarriage, highlighting the role of socio-demographic factors. Keywords: Miscarriage, Monocytes, Consanguinity, Educational Level, Hematological Parameters